2021
DOI: 10.3389/fmicb.2021.712007
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Beta-Lactam-Induced Lysis at the Single-Cell Level

Abstract: Mechanical rupture, or lysis, of the cytoplasmic membrane is a common cell death pathway in bacteria occurring in response to β-lactam antibiotics. A better understanding of the cellular design principles governing the susceptibility and response of individual cells to lysis could indicate methods of potentiating β-lactam antibiotics and clarify relevant aspects of cellular physiology. Here, we take a single-cell approach to bacterial cell lysis to examine three cellular features—turgor pressure, mechanosensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 100 publications
(197 reference statements)
1
11
0
Order By: Relevance
“…The libraries were kept in a −20°C freezer for long‐term storage. Similar to previous work determining growth inhibition (Stokes et al , 2020; Wong et al , 2021a, 2021b), E. coli BW25113 was grown overnight in liquid LB medium in 14 ml Falcon tubes at 37°C with shaking at 300 rpm in a light‐protected incubator, then diluted 1:10,000 in fresh liquid LB, and plated into clear 96‐well flat‐bottom plates (product 9018, Corning, Corning, NY) using 100 μl final working volumes or into clear 384‐well flat‐bottom plates (Corning 3680) using 50 μl final working volumes, with plate type chosen to match the format of the library screened. Compounds were added to a final concentration of 50 μM, and plates were incubated in sealed plastic bags at 37°C without shaking overnight (16 to 24 h).…”
Section: Methodssupporting
confidence: 72%
“…The libraries were kept in a −20°C freezer for long‐term storage. Similar to previous work determining growth inhibition (Stokes et al , 2020; Wong et al , 2021a, 2021b), E. coli BW25113 was grown overnight in liquid LB medium in 14 ml Falcon tubes at 37°C with shaking at 300 rpm in a light‐protected incubator, then diluted 1:10,000 in fresh liquid LB, and plated into clear 96‐well flat‐bottom plates (product 9018, Corning, Corning, NY) using 100 μl final working volumes or into clear 384‐well flat‐bottom plates (Corning 3680) using 50 μl final working volumes, with plate type chosen to match the format of the library screened. Compounds were added to a final concentration of 50 μM, and plates were incubated in sealed plastic bags at 37°C without shaking overnight (16 to 24 h).…”
Section: Methodssupporting
confidence: 72%
“…Treated sacculi were observed to show an altogether less dense peptidoglycan network, most probably due to a loss of murein cross linkage, with structural defects in band formation (Figures and ). This ultimately led to disruptions of entire cell wall patches in less dense regions (Figures and ), presumably due to the incapacity to withstand the high osmotic pressure inside the bacteria, leading to cell lysis . Both septal and cylinder areas were affected by those disruption processes.…”
Section: Resultsmentioning
confidence: 99%
“…Wong et al have reported a method for observing bacterial cells using a microfluidic chamber ( 44 , 45 ). Their setup may allow more readily for the dilution of AMP solution and longer incubation, which would be useful for the single-cell analysis proposed in the present work.…”
Section: Resultsmentioning
confidence: 99%